Sonic and the Tales of Terror: Sonic the Hedgehog # 2 - Phegley, Kiel; Spaziante, Patrick (New York, New York : Penguin Young Readers Licenses, 2018)
"In three tales, the fastest hero alive encounters some of the spookiest threats Dr. Eggman has ever unleashed, including zombified friends, midnight transformations, and mischievous ghosts"--Page [4] of cover.
Night of the unliving -- Spook forest -- Night of the werehog.
At head of title: Sonic the Hedgehog.
"Based on the popular characters in the Sega game Sonic the Hedgehog"--Page [4] of cover.
New kids book 2022 summer.
Keywords: Sonic the Hedgehog -- (Fictitious character) -- Juvenile fiction; Sonic the Hedgehog -- (Fictitious character); Hedgehogs -- Juvenile fiction; Hedgehogs; Adventure stories; Adventure and adventurers -- Fiction; Fiction; Juvenile works; Adventure fiction